Fluid Replacement Therapy and Perioperative Management - Corey-Plett, Pat (Operating Room Nurses Association of Canada Journal, 1994)
Objectives: Physiology of body ﬂuids Fluid therapy Fluid maintenance Fluid replacement Perioperative Considerations Conclusion